The Impact of Extracurricular Activities on Dance Skills of Students of SMP Negeri 34 Kerinci - Hestilia, Wina; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to describe the impact of extracurricular activities on the dancing skills of students at SMP Negeri 34 Kerinci. This type of research is a qualitative research with descriptive method. The object of research is students of SMP Negeri 34 Kerinci. The research instrument is the researcher himself. The results of the study showed that students' dancing skills were seen from their lack of self-confidence when doing dance exercises in extracurricular activities. This can be seen from as long as students get new teaching material, they seem to try and practice it well, students seem to try and practice dancing and always want to try, such as students' interest in the material to be studied, besides that students actively ask questions when they are not clear and don't understand. the results of the evaluation of dance extracurricular activities at SMP Negeri 34 Kerinci proved that out of the 34 people tested, 20 students got an A (very good) grade, 10 students got a B (good) and 4 students got a C (fair). From the results of the overall evaluation, the teacher held a meeting with the school principal so that students who got the highest score (Very Good) were included to take part in the Kerinci Regency FLS2N next year, and had the opportunity to take part in inter-school competitions such as Expo and Pensi. This shows that SMP Negeri 34 Kerinci is progressing.